Violence and insecurity in urban space: an analytical approach based on the ecological framework for violence. - García-Cervantes, Natalia (2021)
Violence and insecurity have become pervasive in urban areas, particularly in Latin America, where this phenomenon represents an obstacle to development.  Seeking to contribute to a more nuanced understanding of urban violence and insecurity, this article presents an analytical framework to organize and understand the different levels of risk factors interacting for the appearance of violence in urban areas.  Based on the case study of Culiacán, Sinaloa (Mexico), the article presents an analysis of the interrelated nature of violence, different manifestations and risk factors leading to its proliferation, with a focus on urban space.  Although the causality of violence is difficult to pinpoint, this framework allows not only to consider violence in a more structured way, but also to appraise the relationships between these phenomena at different levels of risk factors.